2017
DOI: 10.3892/ol.2017.5749
|View full text |Cite
|
Sign up to set email alerts
|

F10, a novel hydatidiform mole-associated gene, inhibits the paclitaxel sensitivity of A549 lung cancer cells by downregulating BAX and caspase-3

Abstract: F10 is a novel hydatidiform mole (HM)-associated gene that was initially identified during a study into the pathogenesis of HMs. However, the role of the F10 gene requires further investigation. Our, previous studies have indicated that F10 may be involved in the malignant transformation of HMs and the development of certain types of adenocarcinoma, and that the overexpression of F10 may lead to excessive proliferation and decreased apoptosis of A549 cells. The present study aimed to investigate whether F10 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…5). Previous studies [30,31] have demonstrated that Bcl-2 and its potent inhibitor Bax served a critical role in regulating the cellular expansion and apoptosis. Upregulated Bcl-2 increases cell survival by interfering with apoptosis, whereas elevated expression of Bax accelerates cell death.…”
Section: Resultsmentioning
confidence: 99%
“…5). Previous studies [30,31] have demonstrated that Bcl-2 and its potent inhibitor Bax served a critical role in regulating the cellular expansion and apoptosis. Upregulated Bcl-2 increases cell survival by interfering with apoptosis, whereas elevated expression of Bax accelerates cell death.…”
Section: Resultsmentioning
confidence: 99%
“…At concentration of 20 µM for 1 , the ratio of G1-phase reached about 67.37%, which was about 12% higher than that of the control (55.75%) [ 17 , 18 ]. These data indicating that 1 may inhibit the growth of A549 cells through inducing apoptosis of tumor cells since G1 phase arrest was more related to cell apoptosis, and pro-apoptotic proteins like Bcl-2 usually plays key roles in accelerating the apoptosis of tumor cells [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…lncRNA XR_001838273.1 acts as a sponge for rno-miR-6318 to regulate Iqgap3 or F10. Numerous study literatures have reported that Cdca3, Mcm10, Mki67, Iqgap3, and F10 are all related to tumor cell proliferation [51][52][53][54][55][56]. Knocking down the expression of these genes could reduce tumor cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%